USE OF HYPNOTEACHING METHODS IN STUDENT SELF-REGULATION - Shintia Dwi Putri; Neviyarni (Literasi Nusantara, 2021)
In general, what happens in the learning process is that the teacher uses pre-existing methods, namely lecturing and monotonous so that students get bored, and make student self-regulation not under control. Then the teacher tries to overcome this by using the hypnoteaching method which is a learning method that suggests the subconscious of students. In this article, using a literature review, it is hoped that through this hypnoteaching method, student self-regulation can be overcome and teachers can apply this method in the learning process.